German intellectuals and the challenge of democratic renewal : culture and politics after 1945 - Forner, Sean A. 1973- (Cambridge Univ. Press, 2014)
"This book examines how democracy was rethought in Germany in the wake of National Socialism, the Second World War and the Holocaust. Focusing on a diverse network of intellectual elites in the immediate postwar years, Professor Forner traces their attempts to reckon with the experience of Nazism and scour Germany's ambivalent political and cultural traditions for materials with which to build a better future. In doing so, he reveals how they formulated an internally variegated, but distinctly participatory vision of democratic renewal - a paradoxical counter-elitism of intellectual elites. Although their projects ran aground on internal tensions and on the Cold War, their commitments fuelled critique and dissent in both East and West Germany in the 1950s. The book uncovers a conception of political participation that went beyond the limited possibilities of the Cold War era and which would influence the political struggles of later decades in Germany and across the globe"..